The Long-Run Behavior of Commodity Prices : Small Trends and Big Variability - Cashin, Paul (IMF Working Papers; Working Paper ;, 2001)
Using the longest dataset publicly available (The Economist's index of industrial commodity prices), we analyze the behavior of real commodity prices over the period 1862-99, and have two main findings. First, while there has been a downward trend in real commodity prices of 1.3 percent per year over the last 140 years, little support is found for a break in the long-run trend decline in commodity prices. Second, there is evidence of a ratcheting up in the variability of price movements. The amplitude of price movements increased in the early 1900s, while the frequency of large price movements increased after the collapse of the Bretton Woods regime of fixed exchange rates in the early 1970s. While there is a downward trend in real commodity prices, this is of little practical policy relevance as it is small and completely dominated by the variability of prices.